Genetic variants associated with type 2 diabetes and adiposity and risk of intracranial and abdominal aortic aneurysms - van 't Hof, Femke Ng; Vaucher, Julien; Holmes, Michael V; de Wilde, Arno; Baas, Annette F; Blankensteijn, Jan D; Hofman, Albert; Kiemeney, Lambertus Alm; Rivadeneira, Fernando; Uitterlinden, André G; Vermeulen, Sita H; Rinkel, Gabriël Je; et al. (Springer Nature, 2017)
Epidemiological studies show that type 2 diabetes (T2D) is inversely associated with intracranial aneurysms (IA) and abdominal aortic aneurysms (AAA). Although adiposity has not been considered a risk factor for IA, there have been inconsistent reports relating adiposity to AAA risk. We assessed whether these observations have a genetic, causal basis. To this end, we extracted genotypes of validated single-nucleotide polymorphisms associated with T2D (n = 65), body mass index (BMI) (n = 97) and waist–hip ratio adjusted for BMI (WHRadjBMI) (n = 47) from genotype data collected in 717 IA cases and 1988 controls, and in 818 AAA cases and 3004 controls, all of Dutch descent. For each of these three traits, we computed genetic risk scores (GRS) for each individual in these case–control data sets by summing the number of risk alleles weighted by their published effect size, and tested whether these GRS were associated with risk of aneurysm. We divided the cohorts into GRS quartiles, and compared IA and AAA risk in the highest with the lowest GRS quartile using logistic regression. We found no evidence for association in IA or AAA risk between top and bottom quartiles for the genetic risk scores for T2D, BMI and WHRadjBMI. However, additional Mendelian randomization analyses suggested a trend to potentially causal associations between BMI and WHRadjBMI and risk of AAA. Overall, our results do not support epidemiological observations relating T2D to aneurysm risk, but may indicate a potential role of adiposity in AAA that requires further investigation.
Keywords: Adiposity; Aged; Aortic Aneurysm, Abdominal; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Humans; Intracranial Aneurysm; Male; Middle Aged; Polymorphism, Single Nucleotide; Journal Article; Research Support, Non-U.S. Gov't; Taverne; Genetics; Genetics(clinical); Journal Article